STRATEGI BADAN PENGELOLALAAN KEUANGAN DAN ASET DAERAH DALAM MENINGKATKAN PENDAPATAN DAERAH DI KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Eljawati Eljawati; Susilawati Susilawati (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2023)
The purpose of this study is to analyze, and find out the obstacles and factors that influence in increasing regional income in the Sumedang Regency Revenue Agency, West Java Province. The research method used is descriptive qualitative by exploring the behavior of the object under study to find an in-depth description of the object under study, and the theory is used as an approach to research problems with primary data sources and secondary data through observation, documentation analysis, in-depth interviews and data validity is carried out by triangulation techniques, checking, checking and confirming between observation results, documentation analysis with interview results, and SWOT analysis. The results of the study show that BAPENDA Sumedang Regency has a strategy in the SO quadrant which means that it can seize existing opportunities by utilizing strengths in order to increase local revenue in Sumedang Regency. However, there are still several obstacles and inhibiting factors identified in order to realize this strategy, including a decrease in awareness of paying taxes. low per capita income, BUMD has not given much profit to the local government. and Gross Regional Domestic Product), Increase in Inflation, increasing number of industries, regional retribution, Results of management of separated regional property.